PELATIHAN PEMBUATAN SABUN CUCI PIRING SEBAGAI PEMBEKALAN KETERAMPILAN KEPADA WARGA BINAAN LEMBAGA PENDIDIKAN KHUSUS ANAK KLAS IIB TANJUNG PATI - Inna Kholidasari; Maria Ulfah; Wenny Marthiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
ABSTRACT The skills improvement is a crucial aspect by the children/teenagers in Lembaga Pendidikan Khusus Anak (LPKA) Klas IIB Tanjung Pati, Lima Puluh Kota Regency, the Province of West Sumatra. These children really need education and trainings that could be used for their life when they are come into community. One of training has been conducted for them by the lecturer Fakultas Teknologi Industri Universitas Bung Hatta and some students. The training was about how to makedish washing liquid . Dish washing liquid is a product that always needed in daily life. This kind of dish washing is more popular than other types. The process of making this washing liquid is very simple and the materials can be obtained easily and the price of the materials are also very cheap. These are the reason why the training was conducted. The training ws followed by a discussion relating to the business of selling the dish washing liquid. Hope the trainingis very useful for the children at PLKA Klas IIB Tanjung Pati.